Past and Future: New Ways in Municipal (Property) Management after Debt Consolidation: In Focus: Towns with County Rights - Hegedűs, Szilárd; Lentner, Csaba; Molnár, Petronella (Public Finance Quarterly, 2023)
The indebtedness of local municipalities is of high concern all over the world. In Hungary, after the beginning of the regime change and especially after the 2004 EU accession, when they were used as own contribution for accessing community investment development resources, bank loans and municipal bonds significantly deteriorated the financial stability of the local governmental system. After the review of the process of the accumulation and consolidation of debts, the study explores, through the example of towns with county rights, the state funding regime, which has replaced the formerly passive, debt-accumulating management and has provided stability and predictability, and the Modern Cities Programme, which is now the mainstay of development policy. Another unique feature of the paper is that it also provides numerical indicators to substantiate the improvement of the revenue structure, profitability, liquidity and capitalisation of towns with county rights. The most important result of the study is that it presents the evolution of the Hungarian local government system, the changes in the regulatory environment, and the changes in the institutional system since 2010. In the empirical research part of the study, towns with county rights are under scrutiny. In the study, we explored the positive effects on asset management, the improving situation, and expected future trends in development policy.